Adaptive unscented transform for uncertainty quantification in EMC large‐scale systems. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to introduce a novel methodology for uncertainty quantification in large‐scale systems. It is a non‐intrusive approach based on the unscented transform (UT) but it requires far less simulations from a EM solver for certain models.Design/methodology/approach – The methodology of uncertainty propagation is carried out adaptively instead of considering all input variables. First, a ranking of input variables is determined and after a classical UT is applied successively considering each time one more input variable. The convergence is reached once the most important variables were considered.Findings – The adaptive UT can be an efficient alternative of uncertainty propagation for large dimensional systems.Originality/value – The classical UT is unfeasible for large‐scale systems. This paper presents one new possibility to use this stochastic collocation method for systems with large number of input dimensions.